Crack Assessment by FEM of AMMC Beam Produced by Modified Stir Casting Method. (2015) - Jena, Pankaj Charan; Parhi, Dayal R.; Pohit, G.; Samal, B.P.
Abstract: Aluminium metal matrix composite (AMMC) are now recognized as important structural materials. It offers attractive properties such as low density, good manufacturability and high specific strength. The samples of AMMC were prepared with modified stir casting method and used for crack analysis. Since the structural parts/components made up of AMMC is more susceptibility for crack failure, a finite element method (FEM) is used to analyze the crack failure. FEM analysis is conducted using rectangular cross-sectional cantilever beam for crack at predetermined positions. The deferent mode shapes and natural frequency of the said beam are analyzed to know the behaviour of the AMMC as a beam structures. The result of crack analysis for AMMC is very encouraging so it can be utilize as the structural material in different applications.